Pengaruh Social Media dalam Membentuk Loyalitas Terhadap Film di Bioskop dengan Mediasi Movie Coolness serta Pengalaman Menonton Film - Yusuf, Farrel; Rahajeng Hadiprawoto, Triana (IPB University, 2023)
In 2022 the Indonesian film industry experienced a revival after two years of being affected by the COVID-19 pandemic. Restrictions imposed during pandemic and the changes of consumer behavior have increased the reliance on social media as information provision channel. The phenomenon also transpires in the practice of movie marketing. The purpose of this study is to examine the utilisation of social media as a movie marketing tool by investigating the mediating effects of movie coolness and cinematic experience on movie loyalty. Moreover, this study focuses on the recent Indonesian highest box office movie, KKN in Dancer Village movie. In doing so, this study integrate a framework of social media information dimensions (i.e., interestingness, value added, information amount, virtual appearance) and social media contents (i.e., advertising and promotion), and analyse their impacts on movie coolness, movie experience, and movie loyalty. This study collected 236 respondents and analyzed the data using SEM (Structural Equation Modeling) using SmartPLS 4.0. The finding suggest that the amount of information and social media content are significant drives of movie experience which lead to a loyaltu to a movie. The results of this study can provide insights to better plan marketing activities of Indonesia movies. In addition, this research contributes to the progress of literature in social media marketing and movie marketing.